Individual Entrepreneurship Orientation for Implementation of Digitalization and Value Creation to Improve MSME Performance - Hassandi, Irfan; Mardiana R (Universitas Medan Area, 2025)
This study investigates the influence of Individual Entrepreneurial Orientation (IEO) on digital tech-nology adoption, value creation, and MSME performance in Jambi City, Indonesia. Using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with 165 respondents, the study examines how IEO drives the use of social media, artificial intelligence (AI), and Big Data, as well as economic and social va-lue creation. The results show that IEO significantly promotes digital adoption and economic value crea-tion, while its effect on social value creation is not significant. In terms of performance, AI and Big Data exhibit significant positive effects, whereas social media shows no effect, reflecting its use mainly for visibility rather than strategic or analytical purposes. Notably, even the significant paths display rela-tively small Beta coefficients, indicating that the influence of digital adoption on performance remains modest. Economic and social value creation similarly do not enhance performance, suggesting that these capabilities have not yet matured into strategic strengths. Overall, the findings emphasize that although entrepreneurial behavior supports early-stage digital adoption, meaningful performance improvements require deeper integration of advanced technologies and stronger organizational capabilities.